Insights From a Mixed Methods Analysis of 3 Health Technologies Used in Patients With Parkinson Disease: Mixed Methods Study - Daniel Pérez-Rangel; Mariana H G Monje; Sylvie Grosjean; Martin Srp; Laura Antunes; Raquel Bouça-Machado; Ricardo Cacho; Sergio Domínguez Rodríguez; John Inocentes; Timothy Lynch; Argyri Tsakanika; Dimitrios Fotiadis; et al. (Journal of Medical Internet Research)
Abstract BackgroundThe transition to a patient-centered integrated care model in Parkinson disease (PD) highlights the crucial role of technology. “Technology-enabled care” (TEC) supports diagnosis, disease tracking, self-care education, and care team communication. However, gaps remain in developing and evaluating patient-centered TEC solutions. ObjectiveThis study aims to evaluate the usability and acceptability of 3 health technologies for PD and discuss the significance of the results. MethodsThis multicenter international study was conducted from December 2020 to September 2023 across 5 tertiary PD centers. Participants included individuals diagnosed with PD who were recruited through these centers. Each participant provided informed consent before enrollment. The study assessed the usability and acceptability of 3 different health technologies designed to support PD management. The System Usability Scale (SUS) was used as the primary quantitative measure, with scores ranging from 0 to 100, with higher scores indicating greater usability. Additionally, participants completed a custom usability and acceptability survey, which included Likert-scale questions and open-ended qualitative feedback. To ensure a comprehensive evaluation, structured user testing sessions were conducted. Participants interacted with each technology under guided conditions, followed by independent use in their home environment for a specified period. Data were collected at baseline and after the trial period to assess any changes in user perception. Qualitative thematic analysis of free-text responses was performed to identify key themes related to user experience, perceived benefits, and challenges. Two independent researchers analyzed the qualitative data to ensure reliability and consistency in theme extraction. ResultsThe study included 43 people with PD, of whom 15 were female. The median age of participants was 67.0 (IQR 59.9‐71.5) years, and the median disease duration was 9.6 (IQR 5.0‐13.7) years. The 3 health technologies demonstrated acceptable usability, with median SUS scores ranging from 74.0 to 82.5. Participants expressed a generally positive attitude toward TEC, with a strong interest in continued use. Users particularly valued confidence in navigating the technology and its role in facilitating disease management. The qualitative analysis highlighted several challenges. Users frequently mentioned the need for improved technical support, clearer instructional materials, and simplified report formats to enhance interpretability. Some participants experienced difficulties with initial setup and required assistance, emphasizing the importance of user-friendly onboarding processes. ConclusionsOur study underscores the importance of incorporating patient perspectives in the development of health technologies for PD. Positive user experiences demonstrate the potential of TEC to enhance disease management, but addressing usability challenges remains critical. Future efforts should focus on refining user interfaces, providing comprehensive technical support, and ensuring clear, accessible instructions to maximize adoption and long-term engagement. By prioritizing these aspects, TEC can play a pivotal role in advancing patient-centered health care solutions for PD.